The One That Got Away: How Macrophage-Derived IL-1β Escapes the Mycolactone-Dependent Sec61 Blockade in Buruli Ulcer - Hall, Belinda S.; Hsieh, Louise Tzung-Harn; Sacre, Sandra; Simmonds, Rachel E. (Frontiers in Immunology, 2022)
Buruli ulcer (BU), caused by Mycobacterium ulcerans, is a devastating necrotizing skin disease. Key to its pathogenesis is mycolactone, the exotoxin virulence factor that is both immunosuppressive and cytotoxic. The discovery that the essential Sec61 translocon is the major cellular target of mycolactone explains much of the disease pathology, including the immune blockade. Sec61 inhibition leads to a loss in production of nearly all cytokines from monocytes, macrophages, dendritic cells and T cells, as well as antigen presentation pathway proteins and costimulatory molecules. However, there has long been evidence that the immune system is not completely incapable of responding to M. ulcerans infection. In particular, IL-1beta was recently shown to be present in BU lesions, and to be induced from M. ulcerans-exposed macrophages in a mycolactone-dependent manner. This has important implications for our understanding of BU, showing that mycolactone can act as the “second signal” for IL-1beta production without inhibiting the pathways of unconventional secretion it uses for cellular release. In this Perspective article, we validate and discuss this recent advance, which is entirely in-line with our understanding of mycolactone’s inhibition of the Sec61 translocon. However, we also show that the IL-1 receptor, which uses the conventional secretory pathway, is sensitive to mycolactone blockade at Sec61. Hence, a more complete understanding of the mechanisms regulating IL-1beta function in skin tissue, including the transient intra-macrophage stage of M. ulcerans infection, is urgently needed to uncover the double-edged sword of IL-1beta in BU pathogenesis, treatment and wound healing.